Le secret médical Étude des obligations de confidentialité des soignants en droit suisse - Erard, Frédéric (sui generis Verlag, 2021)
Medical secrecy is going through a troubled period today. The multiplication of health care providers, technological progress and the pressure of financial policies tend to put pressure on this institution and to redefine its contours. In Swiss law, medical secrecy is now governed by an abundance of legal provisions whose implementation has become complex and unpredictable. After a first part dealing with the historical origins of medical secrecy, its main current factors of influence and its ethical justifications, the book systematically analyzes the multiple duties of confidentiality that may apply to caregivers, their respective limits and their articulation. The study concludes with an analysis of several scenarios for the future of medical confidentiality.